The diagnostic utility of submandibular gland sonography and labial salivary gland biopsy in IgG4-related dacryoadenitis and sialadenitis: Its potential application to the diagnostic criteria. Issue 2 (3rd March 2020) - Sakamoto, Mizuki; Moriyama, Masafumi; Shimizu, Mayumi; Chinju, Akira; Mochizuki, Keita; Munemura, Ryusuke; Ohyama, Keiko; Maehara, Takashi; Ogata, Kenichi; Ohta, Miho; Yamauchi, Masaki; Ishiguro, Noriko; et al.
Abstract: Objectives: In this study, we investigated the diagnostic utility of submandibular gland (SMG) sonography and labial salivary gland (LSG) biopsy as a less invasive procedure for diagnosing IgG4-related dacryoadenitis and sialadenitis (IgG4-DS) Methods: Sixty-eight patients with suspected IgG4-DS by presenting swelling of elevated serum IgG (>1747 mg/dl) and/or swelling glands underwent SMG sonography, LSG biopsy and measurement for serum IgG4. SMG sonographic diagnosis was determined by the following characteristic changes; 'hypoechoic areas of a nodal pattern with high vascularity' and/or 'hypoechoic areas of a reticular pattern in the superficial part'. Results: Thirty-one patients were diagnosed with IgG4-DS, 5 with IgG4-RD unaccompanied by lacrimal and salivary gland lesions, 28 with Sjögren's syndrome, and 4 with malignant lymphoma. The sensitivity, specificity, and accuracy of SMG sonography and LSG biopsy were 100%, 83.8%, 91.2% and 64.5%, 73.8%, 75.0%, respectively. Moreover, those of SMG sonography and LSG biopsy combined with serum IgG4 concentration (>135 mg/dl) were 100%, 94.6%, 97.1% and 64.5%, 91.9%, 79.4%, respectively. Conclusion: LSG biopsy needs to be extremely careful to diagnose IgG4-DS because of its low sensitivity. SMG sonography is sufficient for the diagnosis of IgG4-DS, especially when combined with serologic analysis. Thus, SMG sonography could adapt to the diagnostic criteria of IgG4-DS as a non-invasive method.